Design and Construction of an Arduino - Based Solar Power Parameter-Measuring System with Data Logger - Oladimeji , I.; Adediji , Y. B.; Akintola , J. B.; Afolayan, M. A.; Ogunbiyi, O.; Ibrahim , S. M.; Olayinka , S. Z. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Accurate monitoring and measurement of solar photovoltaic panel parameters are important for solar power plant analysis to evaluate the performance and predict the future energy generation. There are always challenges of getting such data readily available due to huge amount of money to be spent on state of the art equipment or the purchase of reliable satellite weather data. This study aimed at the development of a cost-effective parameter-measuring system for a solar photovoltaic panel using Arduino microprocessor board. The systems measure five parameters, including voltage, current, light intensity, temperature, and pressure. The hardware circuit was designed to link different sensors with the Arduino board and the measured data were in turn were documented into a computer for further analysis. The accuracy of the constructed device was ascertained by comparing the measured parameters with that of conventional standard measuring instruments which shows good agreement. The measured parameters show that the output energy generation from solar photovoltaic panel largely depends on the solar irradiance and temperature